2018
DOI: 10.1186/s12935-018-0601-4
|View full text |Cite
|
Sign up to set email alerts
|

miR-145 and miR-497 suppress TGF-β-induced epithelial–mesenchymal transition of non-small cell lung cancer by targeting MTDH

Abstract: BackgroundMicroRNAs (miRNAs) have been reported to play crucial roles in multiple cancers including non-small cell lung cancer (NSCLC). Here, we investigated the role of miR-145 and miR-497 in TGF-β-induced epithelial–mesenchymal transition (EMT) process of NSCLC.MethodsWe performed quantitative real time PCR (qRT-PCR) to detect the expression level of miR-145 and miR-497 in NSCLC cell lines. Then in the presence/absence of TGF-β, we transfected miRNA mimics or inhibitor into A549 and H1299 cells and investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 36 publications
(36 reference statements)
2
33
0
Order By: Relevance
“…miR‐145 is a newly discovered miRNA, which is significantly less expressed in breast cancer (Ding et al, ), cervical cancer (Sathyanarayanan et al, ), glioma (Xu et al, ), colon cancer (Li et al, ), esophageal cancer (Zhang et al, ), and non‐small‐cell lung cancer (Yin et al, ). The genes regulated by miRNA‐145 are different in different tumors, and the molecular mechanisms of their anti‐cancer effects are also different.…”
Section: Discussionmentioning
confidence: 99%
“…miR‐145 is a newly discovered miRNA, which is significantly less expressed in breast cancer (Ding et al, ), cervical cancer (Sathyanarayanan et al, ), glioma (Xu et al, ), colon cancer (Li et al, ), esophageal cancer (Zhang et al, ), and non‐small‐cell lung cancer (Yin et al, ). The genes regulated by miRNA‐145 are different in different tumors, and the molecular mechanisms of their anti‐cancer effects are also different.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, miRNAs have been revealed that they are involved in a large amount of biological processes, including tumour formation and inflammatory responses in many human diseases [25][26][27]. It is well known that miR-199a-5p has been studied to take part in the progress of cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the upregulation of miR‐183‐5p induced apoptosis and inhibited EMT, proliferation, invasion, and migration by the downregulation of ezrin in human endometrial cancer cells . Collectively, EMT is inhibited by many miRNAs, including miR‐145, miR‐497, miR‐145‐5p, miR‐138, miR‐200a, miR‐200b, miR‐655, miR‐30‐5p, and miR‐32 . In addition, EMT is also promoted by many miRNAs, including miR‐221, miR‐222, miR‐214‐3p, and miR‐181a …”
Section: Small Molecules Against Emtmentioning
confidence: 99%
“…194 Collectively, EMT is inhibited by many miRNAs, including miR-145, miR-497, miR-145-5p, miR-138, miR-200a, miR-200b, miR-655, miR-30-5p, and miR-32. [195][196][197][198][199][200][201] In addition, EMT is also promoted by many miRNAs, including miR-221, miR-222, miR-214-3p, and miR-181a. [202][203][204] The flavonoids rhamnetin from cloves, berries and cirsiliol from Cirsium lineare (Thunb.)…”
Section: Ras Signaling Pathwaymentioning
confidence: 99%